The Role of New Electronic Software in School Learning: Google Classroom as an Example - Hasan, Hind Salah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Digital learning platforms have become central to contemporary education, with Google Classroom widely adopted to streamline instruction and communication. Specific Background: Although its use expanded rapidly during and after the pandemic, empirical evidence on its measurable effects on student performance and user experience remains uneven across contexts. Knowledge Gap: Limited studies have simultaneously assessed both academic outcomes and stakeholder perceptions using robust mixed-method designs. Aims: This study investigates the impact of Google Classroom on student achievement, engagement, and user satisfaction while identifying implementation challenges. Results: Quantitative findings show significant improvements in assignment completion, test scores, and participation among Google Classroom users, while qualitative data reveal strong appreciation for accessibility, timely feedback, and collaborative tools, alongside notable technical difficulties reported by both teachers and students. Novelty: The integration of performance metrics with multi-level experiential data provides a comprehensive evaluation of platform effectiveness beyond conventional usage studies. Implications: The study highlights that Google Classroom can enhance learning efficiency when supported by adequate infrastructure, teacher training, and equitable access, offering evidence to guide policy decisions and best practices in digital learning integration.Highlight : Shows clear improvements in assignment completion, test scores, and overall participation. Emphasizes strong benefits in accessibility, collaboration, and feedback speed. Highlights technical issues as a key barrier requiring better infrastructure and support. Keywords : Google Classroom, e-learning, educational technology, digital pedagogy, student performance